Reformasi Gagal Total, Kawan!: A Stylistics Study of Political Satire in Eka Kurniawan’s Corat-coret di Toilet - Lailatul Maulida (Study Program of Arabic Language Teaching, 2020)
This paper aims to discuss and analyze political satire in Eka Kurniawan's short story titled Corat-coret di Toilet. By applying descriptive qualitative research as well as stylistics approach, researcher then reading the whole text of the short story, analyzing the political satire, and taking notes the sentence related to political satire inside. Found that there are nine sentences of satire in the short story that refer to political satire that was written by some students on the campus toilet's walls against the situation of the government in the year of 1990s where the freedom of conveying aspirations is tightly limited. The ubiquity of political satire in this short story builds critical thinking on the readers and also stimulates them intensely to be able to interpretatively understand what is meant by the political satire, the relation of those political satires with the political and social condition in Indonesia, specifically in the end of New Order and the beginning of reform era. Finally, the political satire in Corat-coret di Toilet reflects legal and social injustice in Indonesia. Nevertheless, Kurniawan's work able to persuade the readers with a sense of humor, sadness, anger and the truth of the Indonesian situation, to understand and care more about social and government phenomena in their own country.